HUBUNGAN KECERDASAN EMOSI DENGAN PENYESUAIAN DIRI PESERTA DIDIK DI SMP NEGERI 20 PADANG - Ichsan, Bayu; Ibrahim, Indra; Gusneli, Gusneli (Bimbingan dan Konseling, 2013)
Lately that already found a variety of problems of teenagers which indicates the inability of adolescents in acclimated and fragile their emotional life. The succession of each person in adaptability is influenced by either good or not that the emotional that they have. This research was use quantitative research with using the form of correlation research. The population of the research was the students of 20 Junior High School Students in Padang with the amounted of the participants are 835 students while the sample amounted to 91 people. Sampling technique that used is stratified random sampling. The data used to analyze is product moment correlation formula of coefficient karl person and then compare it with the table of values of r product moment. The results showed that the students of 20 Junior High School students have a good emotional intelligence as well as their adjustment itself too. While the results regarding the relationship of self adjustment with emotional intelligence obtained rhitung of 0,739 > of rtabel is 0,235 of df 70 with the significant level of 5%. The result of the research was the relationship of emotional intelligence with the adaptability of the students that shows high level of significant.